EFFECT OF CUPPER DOPPING ON THE OPTICAL PROPERTIES OF ZNS THIN FILMS - KALID H. YASEEN; AYED N. SALEH; SABRI J.MOHAMMED (مجلة جامعة الانبار للعلوم الصرفة, 2012)
In this paper thin films of ZnS dopped with cupper has been prepared using thermal chemical spray pyrolysis at (623)K and pressure of (1.2)bar. The optical properties of these films have been measured in the rang(300-900)nm ,different optical properties has shown different behaviour as the wavelength in reuses as explained in the te